Table of Contents Vol 80, No 1 (2024) (HTS teologiese studies, 2024)
This Table of Contents reflects the print compilation of peer-reviewed articles published in the journal. Each article listed was originally published online under the journal’s open access model and remains individually accessible and citable. This compilation has been created solely for print distribution, reference, and archival purposes. No new research content is introduced. The publisher affirms that all articles included in this compilation have undergone the journal’s standard editorial and peer-review processes.